solve this completing method
Attachments:
![](https://hi-static.z-dn.net/files/df5/5cdf27eef47b55919a49603e9e7b48d6.jpg)
Answers
Answered by
1
You have to solve this using the 'discriminant' method.
x2−3x+1=0
Considering the coefficients and constants in the equation
a=1 [Coefficient of x2 ]
b= -3 [Coefficient of x ]
c = 1 [The constant term]
The formula for the discriminant of a quadratic equation is
D=b2−4ac
Substituting values for a, b and c
D=(−3)2−4X1X1
D=9−4
D=5
Now, the formula for finding 'x' using the discriminant is
x = ( −b±√D)/2a
Substituting values for b, D and a in the above formula, you get
x = (3±√5)/2
Hence, the values for 'x' are
x = (3+√5)/2 and (3−√5)/2.
Answered by
5
Answer:
Manguluralli jor bisilu
Similar questions